(untitled) (Al-Qamar, 2022)
The meaning and treatment of jihad are often misunderstood by ordinary people starting from the confusion caused by various parties, Muslims and non-Muslims. An explanation of the true meaning of jihad needs to be made public especially in rejecting the false accusations and statements of Western scholars. In addition, the issue of malignancy which is increasingly widespread in all corners of the world has made the issue of jihad an important and often debated issue. In fact, there are those who link the violence and war that is currently in force with the personality of the Prophet Muhammad, as Robert Spencer did in his writings. Therefore, the main purpose of this study is to analyze and explain the views of the orientalist Robert Spencer in his book, “The Truth about Muhammad.” regarding the misunderstanding of this issue of jihad. Through the method of text analysis which focuses on the theme of jihad in the book. This article has identified several errors and elements of propaganda spread in his writings. All of these negative views may make ignorant and naive readers to hate the Prophet Muhammad (PBUH) for practicing jihad and alienating non-Islamic people instead of knowing Islam through its true perspective.